Contagion accounting - I\~naki Aldasoro; Anne-Caroline Hüser; Christoffer Kok Sørensen (European Central Bank (ECB), 2020)
We provide a simple and tractable accounting-based stress-testing framework to assess loss dynamics in the banking sector, in a context of leverage targeting. Contagion can occur through direct interbank exposures, and indirect exposures due to overlapping portfolios with the associated price dynamics via fire sales. We apply the framework to three granular proprietary ECB datasets, including an interbank network of 26 large euro area banks as well as their overlapping portfolios of loans, derivatives and securities. A 5 percent shock to the price of assets held in the trading book leads to an initial loss of 30 percent of system equity and an additional loss of 1.3 percent due to fire sales spillovers. Direct interbank contagion is negligible in our analysis. Our findings underscore the importance of accurately estimating the price effects of fire sales.
Keywords: C63; G01; G18; G21; 330; Interbank networks; contagion; overlapping portfolios; fire sales; stress-testing